Single Cobalt Sites Dispersed in Hierarchically Porous Nanofiber Networks for Durable and High‐Power PGM‐Free Cathodes in Fuel Cells. Issue 46 (15th October 2020) - He, Yanghua; Guo, Hui; Hwang, Sooyeon; Yang, Xiaoxuan; He, Zizhou; Braaten, Jonathan; Karakalos, Stavros; Shan, Weitao; Wang, Maoyu; Zhou, Hua; Feng, Zhenxing; More, Karren L.; et al.
Abstract: Increasing catalytic activity and durability of atomically dispersed metal–nitrogen–carbon (M–N–C) catalysts for the oxygen reduction reaction (ORR) cathode in proton‐exchange‐membrane fuel cells remains a grand challenge. Here, a high‐power and durable Co–N–C nanofiber catalyst synthesized through electrospinning cobalt‐doped zeolitic imidazolate frameworks into selected polyacrylonitrile and poly(vinylpyrrolidone) polymers is reported. The distinct porous fibrous morphology and hierarchical structures play a vital role in boosting electrode performance by exposing more accessible active sites, providing facile electron conductivity, and facilitating the mass transport of reactant. The enhanced intrinsic activity is attributed to the extra graphitic N dopants surrounding the CoN4 moieties. The highly graphitized carbon matrix in the catalyst is beneficial for enhancing the carbon corrosion resistance, thereby promoting catalyst stability. The unique nanoscale X‐ray computed tomography verifies the well‐distributed ionomer coverage throughout the fibrous carbon network in the catalyst. The membrane electrode assembly achieves a power density of 0.40 W cm −2 in a practical H2 /air cell (1.0 bar) and demonstrates significantly enhanced durability under accelerated stability tests. The combination of the intrinsic activity and stability of single Co sites, along with unique catalyst architecture, provide new insight into designing efficient PGM‐free electrodes with improved performance and durability. Abstract : Atomically dispersed single‐Co‐site catalysts, through electrospinning cobalt‐doped ZIF‐8 crystals, and selected dual polyacrylonitrile and poly(vinylpyrrolidone) polymers are reported. The interconnected porous nanofiber networks with hierarchical architecture are essential to facilitate mass and charge transfer within an electrode, along with uniform ionomer dispersion for the oxygen reduction reaction. The catalyst is highly active and durable in proton‐exchange‐membrane fuel cells.